THE USE OF JIGSAW TECHNIQUE IN IMPROVING STUDENTS' READING COMPREHENSION - Juhaendi, Dzulfiqar Akbar (2013)
In junior high school, teaching reading comprehension is very important in order to help students gain information and knowledge from written sources. A good teaching technique is necessary to improve students' reading comprehension. This study investigated the use of Jigsaw Technique in improving students' reading comprehension and students' responses to the use of the technique. Quasi experimental research was used in this study. The samples of this study were two classes of eight grade students of a junior high school in Bandung; one class became the control group and the other the experimental group. Each class consisted of 42 students. From the findings, it is shown that the implementation of Jigsaw technique failed to improve the students' reading comprehension as indicated by the statistical scores in the post test of the experimental group (M= 74.85), SE (1.54), and the post test of the control group (M=78.73), SE (1.40). The students' responses in the questionnaires and observation proved that learning condition and class management became the causes of the ineffectiveness. In accordance with the result, it is recommended that teachers need to pay attention to the learning condition and class control when deciding to use Jigsaw technique.